Bacteria From the Multi-Contaminated Tinto River Estuary (SW, Spain) Show High Multi-Resistance to Antibiotics and Point to Paenibacillus spp. as Antibiotic-Resistance-Dissemination Players - Eduardo-Correia, Benedito; Morales-Filloy, Héctor; Abad, José P. (Frontiers in Microbiology, 2020)
Bacterial resistance to antibiotics is an ever-increasing phenomenon that, besides clinical settings, is generally assumed to be prevalent in environmental soils and waters. The analysis of bacteria resistant to each one of 11 antibiotics in waters and sediments of the Huelva’s estuary, a multi-contaminated environment, showed high levels of bacteria resistant mainly to Tm, among others. To further gain knowledge on the fate of multi-drug resistance (MDR) in environmental bacteria, 579 ampicillin-resistant bacteria were isolated tested for resistance to 10 antibiotics. 92.7% of the isolates were resistant to four or more antibiotic classes, indicating a high level of multi-resistance. 143 resistance profiles were found. The isolates with different MDR profiles and/or colony morphologies were phylogenetically ascribed based on 16S rDNA to phyla Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes, including 48 genera. Putative intrinsic resistance was detected in different phylogenetic groups including genera Altererythrobacter, Bacillus, Brevundimonas, Erythrobacter, Mesonia, Ochrobactrum, and Ponticaulis. Correlation of the presence of pairs of the non-intrinsic-resistances in phylogenetic groups based on the kappa index (κ) highlighted the co-habitation of some of the tested pairs at different phylogenetic levels. Maximum correlation (κ = 1.000) was found for pairs CzR/TcR in Betaproteobacteria, and CcR/TcR and EmR/SmR in Sphingobacteriia at the class level, while at the genus level, was found for CcR/TcR and NxR/TmR in Mesonia, CzR/TmR and EmR/KmR in Paenibacillus, and CcR/EmR and RpR/TcR in Pseudomonas. These results could suggest the existence of intra-class and intra-genus-transmissible genetic elements containing determinants for both members of each pair. Network analysis based on κ values higher than 0.4 indicated the sharing of paired resistances among several genera, many of them centered on the Paenibacillus node and raising the hypothesis of inter-genera transmission of resistances interconnected through members of this genus. This is the first time that a possible hotspot of resistance interchange in a particular environment may have been detected, opening up the possibility that one, or a few, bacterial members of the community could be important promoters of antibiotic resistance (AR) dissemination in this environment’s bacterial population. Further studies using the available isolates will likely give insights of the possible mechanisms and genetic elements involved.